2018
DOI: 10.21767/2049-5471.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Language Skills and Level of Experience among Arabic-Speaking Healthcare Interpreters in Denmark; an Explorative Study

Abstract: Background: Denmark has become a multicultural society over the past three decades, with 12.8% of the population being immigrants and their descendants. Many of these risk inequality in access to health and in health outcomes because of language barriers. The quality of healthcare interpreting services has recently been discussed by politicians and the media. The present explorative study investigated the sociodemographic characteristics, level of experience and linguistic skills of Arabic-speaking healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…While most of our participants increased their knowledge score after participating in the health introduction course, those with the least interpreting experience increased their knowledge score the most. Itani et al 4 also found that longer interpreting experience was associated with greater likelihood of having adequate language skills for effective communication. The open-ended questions in our project revealed that some of the experienced interpreters felt they did not gain new knowledge or skills from participating in the course, suggesting a need for an additional course aiming at a higher level of interpretation training.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…While most of our participants increased their knowledge score after participating in the health introduction course, those with the least interpreting experience increased their knowledge score the most. Itani et al 4 also found that longer interpreting experience was associated with greater likelihood of having adequate language skills for effective communication. The open-ended questions in our project revealed that some of the experienced interpreters felt they did not gain new knowledge or skills from participating in the course, suggesting a need for an additional course aiming at a higher level of interpretation training.…”
Section: Discussionmentioning
confidence: 95%
“…3 Interpreters' skills and knowledge regarding language, ethics and confidentiality vary considerably. 4 Ad hoc interpreters such as family members and friends are often used in the healthcare sector, 5 with potentially negative consequences for both the patient and the family interpreter. 6,7 Nevertheless, the use of professional medical interpreters is low in many clinical settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the interpreters participating in our study, following training participants were important: (a) knowledge about how and where to get support, (b) supervision in difficult interpreting situations; and (c) knowledge and competencies on how to translate vulnerable diagnoses and sensitive patient situations and reactions. Another Danish study underlined the importance of all interpreters to undergo testing of their linguistic skills, to be able to work professionally as healthcare interpreters (Itani et al., 2017). However, linguistic skills alone are not enough.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates the need for structures in the organization that support healthcare professionals to write incidents reports concerning failure in the interpreter service as a part of systematic quality work [26], because communication is considered as an important area for the improvement of patient involvement in matters of patient safety [33]. Challenges in communication through interpreters have been described as being related to interpreters’ personal characteristics such as linguistic competence [21, 34, 35] and professional attitude and to the organizational context of interpreting practice, including the availability of laws, policy and guidelines [21, 35]. Failure in interpreting practice may lead to inadequate communication, which in turn may cause delayed care [15], limited access to diagnoses, diagnostic testing and treatment [36].…”
Section: Discussionmentioning
confidence: 99%